(untitled) (Prilozi za orijentalnu filologiju, 2017)
An attempt to determine the concept of the Islamic state on the theoretical level meets a number of difficulties. The chief one comes from the fact that even from the early days of Islam there existed simultaneously several Muslim states, which is in a certain sense contrary to the fundamental political requirement of Islam, the ideal of which is state unity of all Muslims. In attempting to give a theoretical definition of the Islamic state it is necessary to start with the fact that Islam was in the beginning a community of believers which gradually developed into a state. Although it developed into a state, Islam continued to function as a community of believers as well. Thus, was created in Islam a certain unity of state and religious community. Hence Islamic law (šerijat) assumed the character of a religious obligation; at the same time, it sanctioned and constituted religion politically. These facts determined in an essential way the character of fundamental Islamic political institutions: that of the caliph as head of state and leader of Muslim religious life, and that of qadi as protector of justice and guardian of the Islamic way of life. These institutions, especially that of the caliphate, underwent a long evolution in the political history of Islam, during which its original meaning and significance gradually faded away.